Responding To Drama: The Efl Students’ Reader-Response Literary Analysis - Febriani, R Bunga; Rohayati, Dedeh; Syafryadin, Syafryadin (Wahana Pendidikan, 2024)
This article presents the EFL students' reader-response literary analysis of an English drama. The study aims to investigate the EFL students' engagement in reading drama as one of the literary genres and the way they make a Reader-Response literary analysis of the drama. The writer carried out the present research by analyzing the students' reflective essays in which they respond to an English drama entitled "The Other Player" written by Owen G. Arno. The study consists of 9 student participants enrolling in the Introduction to Literature subject at an English Education Program of one private university in West Java. Introduction to Literature subject was taught to English as a Foreign Language students in the university and is a subject that introduced the students to literature and literary works and led the students to evaluate, describe, and analyze literary works. In responding the given drama, the students were asked several questions. Then, the students answered the questions based on their interpretation and understanding. The study revealed several findings. The findings of the first part revealed that the students showed active engagement in the reading of drama because they were able to tell their enjoyment of the story, make a relation between the story and the other's life experiences, and make judgments and arguments about the things happened in the story. The finding of the second part revealed that the student participants were able to actualize themselves upon the drama they were reading and put it into the reflective essays or reflections.